Roles of Mn and Co in Ni-rich layered oxide cathodes synthesized utilizing a Taylor Vortex Reactor. (20th September 2021) - Aryal, Shankar; Durham, Jessica L.; Lipson, Albert L.; Pupek, Krzysztof Z.; Kahvecioglu, Ozgenur
Abstract: Layered oxides, composed of nickel, manganese, and cobalt (NMC), are sought after as cathode materials which provide improved energy density, cycle life, and safety in commercial lithium ion batteries (LIBs). Increasing Ni contents higher than 80% can provide even higher practical discharge capacities >200 mAh/g and ~ 4 V discharge potential vs Li/Li +, making them promising cathodes for next generation LIBs. However, rapid capacity fade during cycling and heat-related safety concerns are delaying their successful transition to industry. We report systematic performance optimization of LiNiO2, LiNi0.9 Mn0.1 O2, and LiNi0.9 Co0.1 O2 high Ni layered oxide cathodes synthesized by utilizing a Taylor Vortex Reactor. Co-free LiNi0.9 Mn0.1 O2 cathode showed 200 mAh/g highest discharge capacity at 0.1 C rate with 84% retention after 103 cycles at 0.3C rate while LiNi0.9 Co0.1 O2 cathode showed higher initial but poor cycle life (225 mAh/g highest discharge capacity at 0.1C rate with only 56% capacity retention after 103 cycles at 0.3 C rate. Synchrotron based X-ray diffraction (SXRD), X-ray absorption spectroscopy (XAS) and focused ion beam (FIB) imaging of pristine and cycled cathodes after 103 cycles provided important information on degradation mechanism. The roles of Mn and Co on layered structure formation, charge balance, cationic mixing, and electrochemical performance were elucidated using the crystallographic information from XRD refinement and electronic state analysis from XAS providing valuable information to design future Ni-rich layered oxide cathodes.